Self-Medication practices and its associated factors among undergraduate students of National University Manila : a cross-sectional Study - Javier, Psyar Lysa P.; Maderaje, Precious Lyn L.; Maguddayao, Milka Dea A.; Vipinosa, Kimberly Ann A. (Manila : National University, 2021)
According to Sonam Jain, et.al. (2011), self-medication practice is the selection and use of medications based on self-diagnosed symptoms without consulting a physician or any healthcare professional. Self-medication is a health concern worldwide.
Title page -- Author Note -- Abstract -- Table of contents -- The Problem and its Background -- Review of Related Literature -- Research Methods -- Presentation, Analysis and Interpretations of Data -- Conclusion and Recommendation -- References -- Appendices -- Curriculum Vitae.
Includes bibliographical references.